2020
DOI: 10.3390/cells9102256
|View full text |Cite
|
Sign up to set email alerts
|

ΕGFR/ERβ-Mediated Cell Morphology and Invasion Capacity Are Associated with Matrix Culture Substrates in Breast Cancer

Abstract: Breast cancer accounts for almost one in four cancer diagnoses in women. Studies in breast cancer patients have identified several molecular markers, indicators of aggressiveness, which help toward more individual therapeutic approaches. In triple-negative breast cancer (TNBC), epidermal growth factor receptor (EGFR) overexpression is associated with increased metastatic potential and worst survival rates. Specifically, abnormal EGFR activation leads to altered matrix metalloproteinases’ (MMPs) expression and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…Breast cancer cells' morphological characteristics are useful indicators of the interactions that take place between cells and tumor microenvironment. We have recently showed the importance of the EGFR/ERβ axis in the adhesion and invasion potential of breast cancer cells as well as the development of specific morphological structures (filopodia and extracellular vesicles) in artificial 3D cultures using various ECM substrates [37]. Herein, we assessed the impact of E2 and EGFR inhibition on cell morphology and cytoskeletal organization in standard 2D cultures by scanning electron microscopy (SEM), IF microscopy and AFM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Breast cancer cells' morphological characteristics are useful indicators of the interactions that take place between cells and tumor microenvironment. We have recently showed the importance of the EGFR/ERβ axis in the adhesion and invasion potential of breast cancer cells as well as the development of specific morphological structures (filopodia and extracellular vesicles) in artificial 3D cultures using various ECM substrates [37]. Herein, we assessed the impact of E2 and EGFR inhibition on cell morphology and cytoskeletal organization in standard 2D cultures by scanning electron microscopy (SEM), IF microscopy and AFM.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, EGFR is significantly overexpressed in TNBC, and despite the fact that various clinical trials have targeted the receptor's activation, the results until now have not been promising [52,53]. EGFR and ERb are known to interact and together modulate ECM remodeling of TNBC cells [37]. To that end, in the current study we chose the triple-negative, ERb+ MDA-MB-231 cells, as well as the stably transfected, shERb MDA-MB-231 cell line generated in our laboratories, to showcase the synergistic effects of EGFR and ERb in the aggressiveness and CSC-like capabilities of TNBC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we reported that high ESR2 expression rates have been correlated to decreased overall survival rates in breast cancer patients diagnosed with invasive breast carcinoma. Recent reports indicate that ERb target genes mostly regulate cell survival, movement, and growth (50), and that ERb signaling pathway intersects with EGFR cascade to mediate TNBC cell morphology and stemness (13,15). These data have been corroborated by the strong implication of ERb in EMT process since it acts as EMT promoter by activating the TGFb/Smad3 pathway to promote tumor growth and invasion in metastatic renal cell carcinoma (51).…”
Section: Discussionmentioning
confidence: 91%
“…The discovery of ERb in 1996 as the second nuclear receptor for steroid/thyroid hormones (i.e., 17b-estradiol, E2), after ERa, reserved a new era in the diagnosis, survival estimation and therapeutic targeting of breast cancer (12). While less well established, ERb dynamically communicates with major matrix components, including PGs and epidermal growth factor receptor (EGFR) to stimulate cancer cell behavior, epithelialto-mesenchymal transition (EMT) and stem-like characteristics (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%